Unsteady electro-magneto hydrodynamic flow and heat transfer of two ionized fluids in a rotating system with Hall currents - Linga Raju, Temburu; Venkat Rao, B. (Zielona Góra: Uniwersytet Zielonogórski)
An unsteady flow and heat transmission of ionized gases via a horizontal channel enclosed by non-conducting plates in a rotating framework with Hall currents is examined using electro-magnetohydrodynamic (EMHD) two-fluid heat flow. The Hall current impact is taken into account by assuming that the gases are totally ionized, the applied transverse magnetic field is very strong.
Keywords: unsteady flow; magnetic and electric fields; immiscible flow; plasma; Hall effect; rotating frame; heat transfer; insulating plates